USING FOLKTALES IN IMPLEMENTING TEXT-BASED APPROACH TO IMPROVE STUDENTS’ READING COMPREHENSION ABILITY - Edi Supriadi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura)
This research is an ongoing research of using folktales in implementing text-based approach to improve students’ reading comprehension ability. The students' reading scores have been below or just slightly over the passing grades. The students have difficulties in completing the reading questions assigned by their teacher that range from scanning, skimming to inferring. As a result, the students' participation has been low and they show no interest in the lesson. To solve the problems, the writer will use folktales in implementing